Konsep Dasar Pengembangan Sistem Pendidikan Berbasis Islam dan Sains - Ikmal Ikmal; Zaitun Dotinggulo (IAIN Manado, 2021)
Basic Concepts of Developing an Islamic and Science-Based Education System. From an axiological point of view, science and technology must provide the greatest benefit to human life. This means that science and technology are important instruments in every development process as an effort to realize the benefit of human life as a whole. Thus, science and technology must provide the greatest benefit to human life and not vice versa. To achieve this goal, it is necessary to make an effort to integrate general sciences with Islamic sciences through the development of an education system based on religion and science, so that the general sciences are not value-free or secular. Interdisciplinary approaches and interconnections between religious and general disciplines need to be built and developed continuously without stopping